Solar-Cell Squabble. - Fairley, P.
This article deals with the organic photovoltaics that could be dirt cheap, but their efficiency is in dispute. Spurring all this interest was the promise of a much cheaper and more versatile source of solar power. Unlike traditional semiconductors such as silicon, this newer class of PV employs carbon-based plastics, dyes, and nanostructures and can be manufactured via a printing processthat would be far cheaper than the high-temperature vacuum processing used for inorganics.
Keywords: Carbon-based plastics; Nanostructures; Organic photovoltaics; Solar power; Solar-cell.